1986
DOI: 10.1073/pnas.83.17.6440
|View full text |Cite
|
Sign up to set email alerts
|

Efficient reversion of simian sarcoma virus-transformation and inhibition of growth factor-induced mitogenesis by suramin.

Abstract: Simian sarcoma virus, an acutely transforming primate retrovirus with capacity to induce gliomas and sarcomas in experimental animals, has acquired its transforming properties by transducing the cellular gene sequences that encode one of the constituent chains of platelet-derived growth factor. Suramin, a drug used in the treatment of trypanosomiasis and onchocerciasis, has previously been reported to inhibit the interaction of platelet-derived growth factor with its cell surface receptor. We show here that su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
104
1

Year Published

1993
1993
2000
2000

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 232 publications
(113 citation statements)
references
References 30 publications
8
104
1
Order By: Relevance
“…Ras-transformed V12H10 and K61N10 cells were therefore assayed for their ability to proliferate in the absence of serum for 48 h. The expression of either activated Ha-ras or N-ras resulted in serum-independent growth, with cells proliferating at a rate slightly lower than that observed in the presence of 10% FCS (data not shown). In order to assess the impact of a potential autocrine growth factor mechanism mediating Ras-dependent, serum-independent proliferation, cells were incubated in serum-free DMEM in the presence of increasing concentrations of the growth factor antagonist, suramin (Betsholtz et al, 1986;Kehinde et al, 1995). Suramin blocks the interaction between growth factors and their cognate receptors and its e ects are readily reversible.…”
Section: Expression Of Activated Ras In C3h10t1/2 ®Broblastsmentioning
confidence: 99%
“…Ras-transformed V12H10 and K61N10 cells were therefore assayed for their ability to proliferate in the absence of serum for 48 h. The expression of either activated Ha-ras or N-ras resulted in serum-independent growth, with cells proliferating at a rate slightly lower than that observed in the presence of 10% FCS (data not shown). In order to assess the impact of a potential autocrine growth factor mechanism mediating Ras-dependent, serum-independent proliferation, cells were incubated in serum-free DMEM in the presence of increasing concentrations of the growth factor antagonist, suramin (Betsholtz et al, 1986;Kehinde et al, 1995). Suramin blocks the interaction between growth factors and their cognate receptors and its e ects are readily reversible.…”
Section: Expression Of Activated Ras In C3h10t1/2 ®Broblastsmentioning
confidence: 99%
“…The data is representative of two independent experiments. cated that the serum-independent proliferation of V12H10 cells was sensitive to the actions of suramin (15), a nonspecific growth factor antagonist (13,14). This observation implied that the serum-independent proliferation of V12H10 cells was regulated by an autocrine growth factor(s).…”
Section: Fig 2 a Egfr Inhibitors Block Mapk Activation By V12h10:cmmentioning
confidence: 99%
“…We recently reported that mouse fibroblasts transformed by the minimal expression of activated (G12V)Ha-Ras (V12H10 cells) were unable to proliferate in serum-free medium in the presence of suramin, a growth factor antagonist (13)(14)(15). The constitutive MAPK activity in these cells was completely abrogated by the addition of suramin.…”
mentioning
confidence: 99%
“…Its use in acquired immunodeficiency syndrome was based on its potential inhibition of retroviral reverse transcriptase (9) and on its ability to decrease the binding of human immunodeficiency virus to T cells (10). The polysulfate is thought to exert its anti-tumoral action by impairing the binding of growth factors to the surface receptors of malignant cells (11,12) and by inhibiting angiogenesis (13). It may also have anti-invasive properties, due to the inhibition of heparanases (1).…”
mentioning
confidence: 99%